Fabrication, Microstructure and Properties of Nickel/Epoxy Resin Functionally Graded Materials With Magnetic-Field-Driving Method - Zhan, Tongkang; Chang, Jiasong; Li, Jing (Frontiers in Materials, 2021)
Functionally graded materials are attracting more attention, because of the continuously varying properties in different locations. How to design and fabricate FGMs has become a key and difficult point. In this paper, a magnetic-field-driving method is developed to prepare Ni/epoxy resin FGMs by moving a narrow magnetic field from one end of the sample to the other end with the moving direction perpendicular to the field direction. Ni follows the moving of the magnetic field, and a gradient distribution is obtained. The composition gradients are influenced by Ni content, moving velocity, and also cycle times. The results illustrate that this magnetic-field-driving method is an effective way to prepare FGMs, which is very promising into scientific and technological applications.